Kedudukan Asas Hukum dalam Penyelesaian Sengketa Melalui Arbitrase Berdasarkan Undang-Undang Nomor 30 Tahun 1999 - Supeno Supeno; Muhtar Dahri; Hafid Zakariya (Universitas Batanghari Jambi, 2019)
The enactment of Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution is a step forward in dispute resolution in Indonesia, especially the settlement of disputes in the field of trade in response to the deadlock in the settlement of trade disputes that require resolutions quickly, cheaply, informally, and maintained interests and the secrets of the parties. However, there are still some rules and practices that are not in line with the principle of arbitration law itself. In this paper will be reviewed and analyzed the position of the legal principle used in resolving disputes through arbitration, so it is hoped that these legal principles can be upheld by all interested parties, if there are legal rules and legal practices that are contrary to this legal principle, they can be ruled out.